USING AUTOBIOGRAPHICAL FILMS TO ENHANCE ENGLISH LISTENING SKILLS - Thamsan, Phonchita; Boonsawat, Siriyakorn; Samransamruajkit, Jantarawan; Somanawattana, Chanata; Saisena, Natthapat (Journal of MCU Nakhondhat, 2023)
English listening skills are one of the most important skills for language learning in the 21st century. Listening skills are about building good relationships between people in different societies and cultures to get information and cooperate with each other. However, students struggle to hear unfamiliar vocabulary, listen to long and fast contexts, don’t understand expressions and slang in the contexts they hear. The purpose of this article is to examine the effects of listening to autobiographical English-language films. The sample size was 30 freshman-year students in English program which derived from the purposive sampling. Pre-/Posttest, and quizzes were used to analyze the data by using Repeated Measures ANOVA The study found that students had the highest perception of autobiographies of important people through listening to movies, and there was a statistically significant difference in post-study test scores of 3.10 (F (3.64, 101.88) = 26.06, p < .001, η2 = .48). When comparing the results, it was found that students had an average pre-test score of 4.57 and a post-test average score of 9.03, which was a statistically significant difference (F(3.39, 98.30) = 25.30, p < .001, η2 = .47). Students had significant recognition of all 3 autobiographical terms. Students found it difficult to interpret unfamiliar sentences from a non-native speaker’s accent; hence, there is no difference between pre-/posttest scores in listening sentences section. The perception of famous autobiographies was high due to the enrichment of previous knowledge and the passion of important people to fulfill new knowledge.